We Are All Students: The Bologna Process - Nicole Brigitte Maier (Amsterdam Law Forum, 2010)
Initiated in 1999 through the signing of the Bologna Declaration , the Bologna Process wards creating a European Higher Education Area (EHEA) by 2010.